A design algorithm for ring topology centralized-radio-access-network - Agata, N.; Agata, A.; Nishimura, K. (2013 17th International Conference on Optical Networking Design and Modeling (ONDM), 2013)
To meet the rapidly increasing demand for mobile data traffic, centralized-radio-access-network (C-RAN) has been attracting attention because C-RAN architecture is expected to enable operators to decrease the implementation cost of mobile access networks. There are two possible network topologies for realizing C-RAN architecture; one is tree topology and the other is ring topology. The tree topology is widely used for optical access networks, which is known as a "passive optical network (PON)," because of its low implementation cost. However, considering network resilience against link failures, a ring network is attractive in spite of its high implementation cost compared to that of a tree network. In this paper, we propose a novel design algorithm of the access network having the ring topology for applying to the C-RAN architecture. It can automatically design a ring network having low construction cost, by shortening the total cable construction length, under realistic restrictions.